2017
DOI: 10.1111/pim.12506
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni‐specific immune responses and allergy in Uganda

Abstract: SummaryLow allergy‐related disease (ARD) prevalence in low‐income countries may be partly attributed to helminth infections. In the Schistosoma mansoni (Sm)‐endemic Lake Victoria islands (Uganda), we recently observed positive helminth‐allergy associations, despite low ARD prevalence. To understand how Sm‐induced cytokine and antibody profiles might influence allergic response profiles in this population, we assessed Schistosoma worm (SWA)‐ and egg antigen (SEA)‐specific Th1 (IFN‐γ), Th2 (IL‐5, IL‐13) and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…However, a recent study on a fishing community in Uganda, with a low prevalence of allergy‐related diseases, found a positive correlation between S. mansoni ‐specific Th2 cytokines and atopy, and S. mansoni ‐specific IgE and atopy, respectively. A significant inverse associations were observed in relation to wheeze, keeping with the original hypothesis …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, a recent study on a fishing community in Uganda, with a low prevalence of allergy‐related diseases, found a positive correlation between S. mansoni ‐specific Th2 cytokines and atopy, and S. mansoni ‐specific IgE and atopy, respectively. A significant inverse associations were observed in relation to wheeze, keeping with the original hypothesis …”
Section: Discussionsupporting
confidence: 87%
“…A significant inverse associations were observed in relation to wheeze, keeping with the original hypothesis. 38 Previous reports describe Treg cells, Breg cells and IL-10 to be important for protection by natural infections. 14,[16][17][18][19] We observed that the number of pulmonary Treg cells was increased in the BAL fluid of allergic mice during the challenge phase, which has similarly been reported by others, 36,39 tection from AAI in our hands.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have also looked at how helminth‐induced cytokine profiles may influence allergic immune responses. For example, the investigation conducted on islands endemic for S. mansoni in Lake Victoria, Uganda, found that in a subset of participants, reported wheeze was negatively associated with S. mansoni‐ specific cytokine responses . These observations are in line with the protective effects of helminth infection on allergy‐related outcomes.…”
Section: Helminths and Allergy‐related Outcomes: Immune Mechanisms Inmentioning
confidence: 74%
“…Allergen‐specific IgG4 is often considered as a marker of immune modulation while allergen‐specific IgE as a marker of allergic disease . The IgG4 to IgE ratio can be utilized to determine immune modulation over the allergic response.…”
Section: Helminths and Allergy‐related Outcomes: Immune Mechanisms Inmentioning
confidence: 99%
“…Thus, in this context, its main function appears to be a blocking one, and possibly instrumental in preventing IgE‐mediated inflammation. High levels of anti‐ Ascaris IgG4 have been negatively associated with allergen SPT positivity, while in a S. mansoni ‐endemic area—although higher levels of both IgE and IgG4 were found in infected individuals—a higher ratio of IgE to IgG4 predicted clinical allergic symptoms, just as in allergen‐specific immunotherapy . As many helminth products are homologous to common allergens, IgG4 responses raised against helminth products may also bind and block IgE epitopes on allergens, reducing responses to allergens and directly reducing SPT responses .…”
Section: Helminths and Modulation Of Allergic Disease: The Role Of Immentioning
confidence: 99%